Detecção de escoamento envolvendo gás e petróleo empregando técnicas de monitoramento baseadas em radiação infravermelha - Dutra, Guilherme (2013)
Petroleum is opaque in the visible region of the electromagnetic spectrum and therefore is normally a common sense that optical techniques cannot be used as a noninvasive tool to monitor any physical or chemical phenomena through a petroleum volume. There is, however, a great opportunity when the infrared region of the petroleum optical absorption spectrum given that it is semitransparent and therefore radiation can propagate through a volume containing petroleum or mixture with petroleum. The optical detection is based on the Beer-Lambert Law: the electromagnetic spectrum emitted by an optical source, crossing through the absorber undergoes exponential decay in intensity corresponding to the optical path, the concentration of the substance and its absorption coefficient. However, in certain cases, other optical effects such as reflection and refraction predominate, leading to light attenuation that is not understood only by the study of absorption. To understand these results it is implemented a mathematical model of the air bubbles flowing inside a petroleum volume. It is worth pointing out that the IR region of the electromagnetic spectrum can be understood via optical as well as thermal phenomena. To understand the limits of each effect a study of the influence of the temperature variation on the optical detection of petroleum is performed. The flow of air bubbles in static petroleum is studied and a flow loop for air and oil is designed and tested and the flow is measured by the IR monitoring system. The flow of bubbles is observed through 12 mm length of petroleum. These results were obtained without using optimized components and it is concluded that transmission through longer paths is possible. In conclusion, it is possible to detect, by a non -intrusive technique, the two-phase flow involving the petroleum and air employing monitoring techniques based on infrared radiation. The results are promising and should result in the development of instrumentation for potential application in the field for characterizing flow involving petroleum and other substances such as water, CO2, H2S, natural gas and others. Keywords (letras minúsculas separadas por vírgulas): infrared, petroleum, CO2, multiphase flow.